PERHITUNGAN DAN PENGELOLAAN FOOD COST UNTUK MEMAKSIMALKAN PROFITABILITAS USAHA FUWA CHEESECAKE - Kevin Ferdinand Saputra; Agustin Ekadjaja (Jurnal Serina Abdimas, 2025)
The culinary industry sector is classified as a business field that offers a high level of profitability. Consequently, the calculation of food costs constitutes a critical determinant in enhancing business profitability. Business owners are required to conduct comprehensive production cost analyses during the manufacturing process in order to establish selling prices that are both appealing to consumers and competitive within the market. By analyzing production costs and sales data, this study aims to elucidate the relationship between raw material expenses and the menu item of Fuwa Cheesecake, namely Pudding Cheesecake. The implementation of an effective cost-calculation approach is expected to contribute significantly to the improvement of overall business profitability. The findings of this study reveal that the food cost calculation and management practices employed by Fuwa Cheesecake demonstrate a relatively high percentage, ranging between 41%-42%. Furthermore, this research provides insights into the application of strategic approaches to food cost calculation and management that may be utilized by culinary entrepreneurs to attain optimal profitability. It is anticipated that the results of this study will serve as a reference for both prospective and existing business practitioners in formulating and implementing effective food cost strategies aimed at maximizing business profitability. Sektor industri kuliner termasuk dalam kategori usaha yang menawarkan profitabilitas yang tinggi. Oleh sebab itu, perhitungan food cost menjadi faktor utama dalam membantu meningkatkan profitabilitas usaha. Pemilik usaha perlu melakukan perhitungan biaya produksi pada proses produksi untuk menetapkan harga jual yang dapat menarik minat konsumen dan memiliki harga yang kompetitif di pasar. Melalui perhitungan biaya produksi dan data penjualan dari informasi yang telah diperoleh, penelitian ini menjelaskan hubungan biaya bahan baku dengan menu usaha Fuwa Cheesecake yaitu pudding cheesecake. Melalui pelaksanaan perhitungan yang efektif, akan meningkatkan profitabilitas usaha secara signifikan. Hasil penelitian menunjukkan bahwa perhitungan dan pengelolaan food cost yang dilakukan oleh usaha Fuwa Cheesecake menunjukkan persentase yang cukup tinggi, berkisar 41 - 42%. Kemudian, penelitian ini membantu menjelaskan penerapan strategi perhitungan dan pengelolaan food cost yang dapat dilakukan oleh pemilik usaha kuliner untuk mencapai profitabilitas yang diinginkan. Melalui penelitian ini, diharapkan para calon pelaku usaha dan pelaku usaha dapat menerapkan strategi perhitungan dan pengelolaan food cost guna memaksimalkan profitabilitas usahanya.